Analysis of neurosurgical procedures with unplanned reoperation for quality improvement: A 5-year single hospital study. Issue 52 (30th December 2021) - Huang, Wei-Chao; Chen, Yin-Ju; Lin, Martin Hsiu-Chu; Lee, Ming-Hsueh
Abstract : Abstract: The unplanned return to the operating room rate is a quality metric for assessing hospital performance. This study aimed to evaluate the cause, incidence, and time interval of unplanned returns in index neurosurgical procedures within 30 days of the initial surgery as an internal audit. We retrospectively analyzed neurosurgical procedures between January 2015, and December 2019, in a single regional hospital. The definition of an unplanned return to the operating room was a patient who underwent two operations within 30 days when the second procedure was not planned, staged, or related to the natural course of the disease. A total of 4365 patients were identified in our analysis, of which 93 (2%) had an unplanned return to the operating room within 30 days of their initial surgery during admission. The most common reason for an unplanned return to the operating room for a cranial procedure was hemorrhage, followed by hydrocephalus and subdural effusion, which accounted for 49.5%(46/93), 12%(11/93), and 5.4%(5/93) of cases, respectively. In spinal procedures, the most common cause of return was a residual disc, followed by surgical site infection, which accounted for 5.4%(5/93) and 4.3%(4/93) of cases, respectively. The overall median time interval for unplanned returns to the operating room was 3 days (interquartile range, 1–9). Lowering the rate of postoperative hemorrhage in cranial surgery and postoperative residual disc in spine surgery was crucial as an internal audit in a 5-year single institute follow-up. However, the unplanned reoperation rate is less helpful in benchmarking because of the heterogeneity of patients between hospitals.